Natural Compounds against Alzheimer's Disease: Molecular Recognition of Aβ1–42 Peptide by Salvia sclareoides Extract and its Major Component, Rosmarinic Acid, as Investigated by NMR. Issue 3 (9th January 2013) - Airoldi, Cristina; Sironi, Erika; Dias, Catarina; Marcelo, Filipa; Martins, Alice; Rauter, Amélia Pilar; Nicotra, Francesco; Jimenez‐Barbero, Jesus
Abstract Amyloid peptides, Aβ1–40 and Aβ1–42, represent major molecular targets to develop potential drugs and diagnostic tools for Alzheimer's Disease (AD). In fact, oligomeric and fibrillar aggregates generated by these peptides are amongst the principal components of amyloid plaques found post mortem in patients suffering from AD. Rosmarinic acid has been demonstrated to be effective in preventing the aggregation of amyloid peptides in vitro and to delay the progression of the disease in animal models. Nevertheless, no information is available about its molecular mechanism of action. Herein, we report the NMR characterization of the interaction of Salvia sclareoides extract and that of its major component, rosmarinic acid, with Aβ1–42 peptide, whose oligomers have been described as the most toxic Aβ species in vivo. Our data shed light on the structural determinants of rosmarinic acid–Aβ1–42 oligomers interaction, thus allowing the elucidation of its mechanism of action. They also provide important information for the rational design of new compounds with higher affinity for Aβ peptides to generate new anti‐amyloidogenic molecules and/or molecular tools for the specific targeting of amyloid aggregates in vivo. In addition, we identified methyl caffeate, another natural compound present in different plants and human diet, as a good ligand of Aβ1–42 oligomers, which also shows anti‐amyloidogenic activity. Finally, we demonstrated the possibility to exploit STD‐NMR and trNOESY experiments to screen extracts from natural sources for the presence of Aβ peptide ligands.